Pre‐hospital and retrieval medicine: Clinical governance and workforce models. (5th April 2017) - Kennedy, Marcus; Elcock, Mark; Ellis, Daniel; Tall, Gary
Abstract: Pre‐hospital and retrieval medicine (PHARM) has developed significantly in the past decade. This perspective article proposes that PHARM should develop with a clear focus on contemporary health governance principles, and that its workforce and models of care adopt modern interdisciplinary approaches. Many of the older systems of managing clinical standards, and outdated cultural approaches to professional 'turf', workforce and scope of practice have little place in high‐performance organisations. This paper calls us to attention with a recommendation that best and safest systems of care, structured to optimise patient outcomes and system performance should be our goal.